Trichoderma spp. Genes Involved in the Biocontrol Activity Against Rhizoctonia solani - Abbas, Aqleem; Mubeen, Mustansar; Zheng, Hongxia; Sohail, Muhammad Aamir; Shakeel, Qaiser; Solanki, Manoj Kumar; Iftikhar, Yasir; Sharma, Sagar; Kashyap, Brijendra Kumar; Hussain, Sarfaraz; del Carmen Zuñiga Romano, Maria; Moya-Elizondo, Ernesto A.; et al. (Frontiers in Microbiology, 2022)
The fungus Rhizoctonia solani is one of the pathogens that cause considerable harm to plants worldwide. R. solani survives in the soil in the absence of hosts by developing sclerotia, and management practices like breeding for resistant cultivars, crop rotations, and fungicide applications are insufficient and/or ineffective to manage diseases caused by R. solani. One of the most challenging problems facing agriculture in the twenty-first century is the impact of global warming. Environmentally friendly techniques of crop production and improved agricultural practices are essential for long-term food security. Trichoderma spp. could serve as an excellent example of a model fungus to enhance crop productivity in a sustainable way. Among other biocontrol mechanisms, antibiosis, competition, and mycoparasitism are the main mechanisms by which Trichoderma spp. react to the presence of R. solani, thereby preventing or obstructing its proliferation. Additionally, Trichoderma spp. induce a mixed induced systemic resistance or systemic acquired resistance type of resistance in plants against R. solani, known as Trichoderma-induced systemic resistance. Stimulation of every biocontrol mechanism involves Trichoderma spp. genes responsible for encoding secondary metabolites, cell wall degrading enzymes, siderophores, signaling molecules, and plant growth regulators. This review summarizes the Trichoderma spp. genes involved in the biological control activity against R. solani. It also sheds light on Trichoderma-induced systemic resistance in plants against the pathogen. Nonetheless, fast-paced current research on Trichoderma spp. is required to properly utilize their true potential against diseases caused by R. solani.